Multilateral Governance and Conflict Resolution: Pathways to Sustainable Peace - Bernardianto, R. Biroum (Indonesian Scientific Publication, 2025)
This study provides a comprehensive narrative review of multilateral governance and its role in conflict resolution, focusing on global and regional mechanisms of peacebuilding and security. The objective was to examine how international and regional organizations address complex security challenges and to identify the systemic barriers that constrain their effectiveness. A systematic methodology was applied, drawing on peer-reviewed studies retrieved primarily from Scopus and Web of Science using key terms such as